UPGRADING ELEMETARY SCHOOL TEACHERS’ COMPETENCE IN KLUNGKUNG DISTRIC IN DESIGNING AND IMPLEMENTING AUTHENTIC ASSESSMENT - I Nengah Astawa; Ida Bagus Nyoman Mantra; Luh Ketut Sri Widhiasih; Dewa Ayu Ari Wiryadi Joni (Journal on Studies in English Language Teaching (JOSELT), 2020)
The present study was devoted to the implementation of a community service to Elementary school teachers aiming at improving the teachers’ competence in designing and implementing authentic assessment. Participants of this activity were the elementary school teachers in Klungkung district in which the total number was 35 teachers. Before the training started, the teachers were given preliminary test to determine the extent of the ability or competences of teachers on authentic assessment. After figuring out the initial abilities and identifying the needs of the teachers on authentic assessment, then the training was conducted. The results of the final test showed that the ability of teachers in designing and implementing authentic assessment increased significantly. In addition, interviews and questionnaires showed that the motivation of teachers on designing and conducting authentic assessment also increased positively.